8 Immune correlates associated with clinical outcomes in patients with advanced malignancies treated with avelumab and OX40 agonist. (10th December 2020) - Naing, Aung; Karp, Daniel; Piha-Paul, Sarina; Haymaker, Cara; Parra, Edwin; Yang, Fei; Pant, Shubham; Hong, David; Fu, Siqing; Yap, Timothy; Stephen, Bettzy; Yang, Yali; et al.
Abstract : Background: We evaluated immune correlates of avelumab in combination with PF-04518600 (OX40 agonist) in a phase I/II study (NCT03217747 ) in patients with advanced malignancies. Methods: Eligible patients received intravenous avelumab 10 mg/kg and PF04518600 100 mg every 2 weeks in a 4-week cycle. Initially, patients received avelumab from cycle3 day1 (C3D1), later from cycle1 day15 (C1D15). Response was assessed per RECIST 1.1 and irRECIST. Peripheral blood and tumor tissue were obtained from patients at pre-treatment, post-OX40, and post-combo for correlative studies. Translational assays include immunohistochemistry (IHC: PD-L1, OX40 and CD139), multiplex immunofluorescence (mIF: PD-L1/P-1 axis and T-cell activation/regulatory panels), and Nanostring (panCancer Immune Panel) for tumor tissues, and flow cytometry performed on peripheral blood. Fisher's exact test was used to compare response between the two treatment schedules. Log-rank test was performed to test the difference in overall survival (OS) and progression-free survival (PFS) between groups. Linear mixed-effect model was used to estimate the effect of schedule and treatment (time) effects on flow and IHC mIF biomarkers. Results: Twenty-eight patients were treated, 12 received avelumab from C3D1 and 16 from C1D15. Patient characteristics are summarized in table 1 and response data in table 2 . The median follow-up time was 17.8 months. The median OS was 7.9 months and PFS was 3.2 months. Patients on C3D1 schedule had superior PFS than patients on C1D15 schedule (4.6 months vs 2.5 months; P=0.032). The biomarkers associated with survival were investigated in the C3D1 group. Patients with following baseline biomarker characteristics had superior PFS (table 3 ): lower density of total cells expressing CD137 (6.0 vs 3.2 months, P=0.047) and lower percentage of malignant cells expressing OX40+ (5.8 vs 3.2 months, P=0.024). Patients with superior OS had higher frequencies of CD86+HLA-DR+CD141 dendritic cells and CD3+ cells in circulation at baseline (17.2 vs 7.9 months, P=0.012) (table 4 ). This combination was not found to expand circulating T regulatory cells. Early data suggests that while higher neutrophil score correlates with PD, higher exhausted CD8+ T cell score correlates with SD. More translational data will be presented at the conference. Conclusions: With limited data, there is evidence that patients receiving avelumab from C3D1 in combination with PF-04518600 have better response. Antigen presentation machinery showed changes but remained overall intact within the tumor with baseline circulating CD141+CD86+HLA-DR+ DCs positively correlating with OS. Additional studies to evaluate the effect of T-cell agonist on their receptors on malignant cells are needed. Trial Registration: NCT03217747 Ethics Approval: The study was approved by The University of Texas MD Anderson Cancer Center Institutional Review Board (FWA #: 00000363).